An evaluation of the optimality of frequent verification for vertically integrated systems. Issue 1 (7th December 2020) - Kulkarni, Aditya U.; Salado, Alejandro; Xu, Peng; Wernz, Christian
Abstract: Verification activities, such as inspection, testing, analysis, and demonstration, improve one's confidence in the system meeting the system requirements during the development process. Frequent verification is often advocated as a strategy that minimizes costs of rework over the entire design process, where frequent verification involves verifying after any change in the design. However, this strategy is yet to be validated. In this paper, we develop a belief‐based model of verification in systems design to determine the conditions under which frequent verification is an optimal strategy for a vertically integrated organization. Our model uses belief distributions to capture the organization's dynamic confidence in the system design meeting a requirement of interest during the development process. It also captures the organization's dynamic confidence in the correctness of its development activities (or design process) as a function of past verification activities and current system maturity. The analysis of our model shows that frequent verification is a cost‐minimizing strategy for any level of belief in satisfying the requirement only when the organization has high confidence in the correctness of its design activities and the expected cost to rework a faulty design is greater than the costs to set up the verification activities throughout the development process. Otherwise, strategies with infrequent verification are superior. Our work contributes to the growing body of literature on the theoretical foundations of systems engineering and engineering design and seeks to provide practitioners with a means to determine optimal verification strategies.